The therapeutic effect of Huazhuojiedu decoction on precancerous lesions in a gastric cancer model via the regulation of lnc 517368. (30th January 2022) - Hao, Xinyu; Zhou, Pingping; Yang, Zeqi; Yang, Tianxiao; Wang, Yangang
Abstract: Ethnopharmacological relevance: Huazhuojiedu decoction, a Chinese herbal preparation, has been proven to be clinically effective in treating precancerous lesions in gastric cancer (PLGC). This formula is optimized from a classic formula called "Ganluxiaodu Dan." Although some experiments have shown that Huazhuojiedu decoction is effective against PLGC, the mechanism remains unclear. Aim of the study: To investigate the treatment of PLGC with Huazhuojiedu decoction from the perspective of lncRNA in vitro and in vivo . Materials and methods: A PLGC rat model was prepared and randomly divided into a Huazhuojiedu decoction group (HG), a vitacoenzyme group (VG), a model group (MG), and a normal group (CG). Each group was given a corresponding concentration of medicine and distilled water for 10 weeks. The pathological changes in the gastric mucosa were observed by hematoxylin-eosin staining (HE). High-throughput sequencing was performed to detect the differentially expressed lncRNAs in the HG, MG, and CG. Quantitative real-time reverse transcription-polymerase chain reaction (RT-qPCR) was used to verify differentially expressed lncRNAs, and rat–human homology information was obtained from the University of California, Santa Cruz (UCSC) Genome Database. Human gastric mucosal epithelial cells (GES-1) were used to prepare precancerous lesions of gastric cancer cells (MC). A Huazhuojiedu decoction drug-containing serum was prepared to treat the MC cells. The effects of the Huazhuojiedu decoction and the lncRNA ENST00000517368 ( lnc 517368 ) knockdown or overexpression on PLGC cell proliferation and apoptosis were evaluated in vitro using CCK-8, flow cytometry, and RT-qPCR. Results: The HE results showed that gastric mucosal pathology was significantly improved in the HG. High-throughput sequencing results showed that compared with the CG, 91 lncRNAs upregulated in the MG were restored and downregulated in the HG ( P < 0.05), and 115 lncRNAs downregulated in the MG were restored and upregulated in the HG ( P < 0.05). The results of RT-qPCR were consistent with the sequencing results. The differentially expressed genomic rat lncRNA ENSRNOT00000079699 is homologous to human lnc 517368 . In cell experiments, high expression of lnc 517368 promoted proliferation and reduced apoptosis in PLGC cells, while the Huazhuojiedu decoction reduced the expression of lnc 517368 and improved cell morphology. Conclusions: Huazhuojiedu decoction inhibited cell proliferation and promoted apoptosis in PLGC cells, and its effect may be partially dependent on the downregulation of lnc 517368 . Graphical abstract: Image 1